Identidade, memória e narrativas na dança de São Gonçalo do povoado Mussuca (SE) - Bomfim, Wellington de Jesus (2007)
This study deals with the participation of the dance of São Gonçalo of the Mussuca town/SE, in the process of construction of the ethnic identity among this social group. The Mussuca is a grouping recognized as afro-descendents, linked with black enslaved people in the valley of the Cotinguiba region. The collective memory functions as a drive of this linking with the past and if it makes to elaborate narratives on this descent. The objective of this study was to investigate the ways the rite went through to constitute itself as an element of ethnic representation. Internal and external agents had been identified who had participated in different contexts. By means of an ethnographic work we ve reached some aspects of the local structure social which demonstrated the contradictions through the social relations of the group. This process of ethnic autorecognition presents the kinship and the space question as definers of the social arrangements which establish its ethnic boundaries